Increase the economic potential of the Ambulu Community by providing appropriate batik drying technology (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
One of the MSMEs developed Batik as a regional product is Rezti's Batik. Rezti's Batik is located in Ambulu, Jember Regency, about 28.4 km from the University of Jember. Increasing the number of consumer orders has made Rezti's Batik production continue to increase. One of the obstacles faced by Rezti's Batik is the process of making Batik which takes a long time because the drying process still relies on heat from the sun, which takes 4-6 hours. The process can also take longer if the rainy season slows the production process's completion. The solution method is the manufacture of appropriate technology in the form of installing a batik cloth dryer. The batik cloth drying installation implementation at Rezti's Batik is a drying system that utilizes heat from the furnace in the sagging process as a heating medium. The designed dryer consists of a stove as a heat generator which will later be distributed with air from the blower so that the hot air will spread evenly throughout the room.